The Need for Structured Strategies to Improve Stroke Care in a Rural Telestroke Network in Northern New South Wales, Australia: An Observational Study - Kashida, Yumi Tomari; Garcia-Esperon, Carlos; Lillicrap, Thomas; Miteff, Ferdinand; Garcia-Bermejo, Pablo; Gangadharan, Shyam; Chew, Beng Lim Alvin; O'Brien, William; Evans, James; Alanati, Khaled; Bivard, Andrew; Parsons, Mark; et al. (Frontiers in Neurology, 2021)
Introduction: A telestroke network in Northern New South Wales, Australia has been developed since 2017. We theorized that the telestroke network development would drive a progressive improvement in stroke care metrics over time. Aim: This study aimed to describe changes in acute stroke workflow metrics over time to determine whether they improved with network experience. Methods: We prospectively collected data of patients assessed by telestroke who received multimodal computed tomography (mCT) and were diagnosed with ischemic stroke or transient ischemic attack from January 2017 to July 2019. The period was divided into two phases (phase 1: January 2017 – October 2018 and phase 2: November 2018 – July 2019). We compared median door-to-call, door-to-image, and door-to-decision time between the two phases. Results: We included 433 patients (243 in phase 1 and 190 in phase 2). Each spoke site treated 1.5–5.2 patients per month. There were Door-to-call time (median 39 in phase 1, 35 min in phase 2, p = 0.18), and door-to-decision time (median 81.5 vs. 83 min, p = 0.31) were not improved significantly. Similarly, in the reperfusion therapy subgroup, door-to-call time (median 29 vs. 24.5 min, p = 0.12) and door-to-decision time (median 70.5 vs. 67.5 min, p = 0.75) remained substantially unchanged. Regression analysis showed no association between time in the network and door-to-decision time (coefficient 1.5, p = 0.32). Conclusion: In our telestroke network, acute stroke timing metrics did not improve over time. There is the need for targeted education and training focusing on both stroke reperfusion competencies and the technical aspects of telestroke in areas with limited workforce and high turnover.